Proceedings of the 40th International ACM SIGIR Conference on Research and Development in Information Retrieval 2017
DOI: 10.1145/3077136.3084153
|View full text |Cite
|
Sign up to set email alerts
|

Health Misinformation in Search and Social Media

Abstract: Personal user groups. For each characteristic a box plot (excluding outliers outside 90th percentile) is shown with median values under the title. Differences in medians are tested using Mann-Whitney U test, for which p-values, Bonferroni adjusted for multiple hypothesis testing, are shown on the corresponding lines spanning the two variables being compared: p < 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 84 publications
0
17
0
Order By: Relevance
“…However, online sources also contain misinformation that may negatively affect attitudes and behavior and, as such, may have extremely harmful effects on public health [ 5 ]. In addition, health misinformation, which is against established medical understanding [ 6 ], may be widely distributed in order to reach a large population in a short time in the digital age [ 7 ]. This is extremely important because previous studies have shown that many parents mostly receive vaccination information through online sources [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, online sources also contain misinformation that may negatively affect attitudes and behavior and, as such, may have extremely harmful effects on public health [ 5 ]. In addition, health misinformation, which is against established medical understanding [ 6 ], may be widely distributed in order to reach a large population in a short time in the digital age [ 7 ]. This is extremely important because previous studies have shown that many parents mostly receive vaccination information through online sources [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ghenai and Mejova [10] collected 13,728,215 tweets concerning Zika from January to August 2016. Tweets were annotated as debunking a rumor, supporting a rumor, or neither.…”
Section: Introductionmentioning
confidence: 99%
“…The third model suggests that examining a collection of trust indicators from data analysis is the ideal approach to predicting trustworthiness, in a model where personalized solutions for clusters of users can also be supported [4]. The final model examines rumour spread in social networks such as Twitter, using crowdsourcing to help to identify false information for applications such as health discussion boards [5,30,31].…”
Section: Results: Artificial Intelligence Trust Modeling To Detect Misinformationmentioning
confidence: 99%
“…The first social network we explored in more detail was Twitter. This was the network examined in the work of Ghenai [5,30,31] which employed crowdsourcing to assist in obtaining labelled data (used when training learning algorithms to detect misinformation). That study was restricted to the healthcare domain, where expert opinion was also available.…”
Section: Twittermentioning
confidence: 99%